DESIGN OF PASSANGER TERMINAL OF SULTAN THAHA AIRPORT - Gisela Winata, Fransisca
In this paper, the structure is designed with high risk category as an airport passenger terminal. This structure is designed with high risk category because of considering safety for the pessangers and after damage happened, passenger terminal still can be operated. Also, this structure is designed using Intermediate Moment Resisting Frames (SRPMM) which is referring to berupa SNI 1729:2015, SNI 1726:2019, SNI 1727:2018, dan SNI 2847:2019. This structure works as a reinforced concrete structure for the building and a steel truss structure for the roof. For the modelling that is done, using help from software such as ETABS 2017 and SAP2000 v21, while for structure element structure detailing, using SPColumn and SAFE 2016. The structure that is designed is expected to be capable in withstanding dead load (DL), superimposed dead load (SIDL), live load (LL), earthquake load, and deformation boundary.